Global trends in intelligent computing research and development - Tripathy, B. K., 1957-; Acharjya, D. P., 1969-; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., USA) : IGI Global, 2014)
'This book brings together recent advances and indepth knowledge in the fields of knowledge representation and computational intelligence, highlighting the theoretical advances and their applications to real life problems'--Provided by publisher.
Clustering-based stability and seasonality analysis for optimal inventory prediction / Manish Joshi, Pawan Lingras, Gajendra Wani, Peng Zhang -- Efficient color image segmentation by a parallel optimized (ParaOptiMUSIG) activation function / Sourav De, Siddhartha Bhattacharyya, Susanta Chakraborty -- Learning using soft computing techniques / V. Susheela Devi -- Chaotic map model-based interference employed in quantum-inspired genetic algorithm to determine the optimum gray level image thresholding / Sandip Dey, Siddhartha Bhattacharyya, Ujjwal Maulik -- Feature selection algorithms for classification and clustering in bioinformatics / Sujata Dash, Bichitrananda Patra -- Soft subspace clustering for cancer microarray data analysis: a survey / Natthakan Iam-On, Tossapon Boongoen -- Multi-objective genetic and fuzzy approaches in rule mining problem of knowledge discovery in databases / Harihar Kalia, Satchidananda Dehuri, Ashish Ghosh -- Rough sets and approximate reasoning / B. K. Tripathy -- Case-based reasoning and some typical applications / Durga Prasad Roy, Baisakhi Chakraborty -- Hybrid genetic algorithm: an optimization tool / Kedar Nath Das -- Knowledge representation using formal concept analysis: a study on concept generation / Ch. Aswani Kumar, Prem Kumar Singh -- Heterogeneous data structure'r-Atrain' / Ranjit Biswas -- Comparative analysis of hybrid soft set methods / Debadutta Mohanty -- Diagram drawing using Braille text: a low cost learning aid for blind people / Anirban Mukherjee, Utpal Garain, Arindam Biswas -- Application of functional approach to lists for development of relational model databases and Petri net analysis / Sasanko Sekhar Gantayat, B. K. Tripathy -- Soft sets: theory and applications / Pinaki Majumdar -- Adaptive and neural pH neutralization for strong acid-strong base system / J. Abdul Jaleel, Anish Benny, David K. Daniel -- A Shannon-like solution for the fundamental equation of information science / Alexandre de Castro.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 12/26/2013).
Keywords: Engineering -- Data processing; Science -- Data processing; Artificial intelligence; Algorithms for knowledge representation; business intelligence; Data preprocessing; Engineering science; Feature selection/instance; Knowledge discovery in databases; Outlier detection; Rough-fuzzy computing; Swarm intelligence; Theoretical foundations